Optimization of the surgical arteriovenous fistula for end-stage renal disease - David B. Kingsmore, MD, FRCS, Mb ChB, BMEdBiol; Ben Edgar, FRCS, Mb ChB; Karen Stevenson, PhD, FRCS, Mb ChB, BSc (MedSci) (JVS-Vascular Insights)
Objective: It is widely acknowledged that an arteriovenous fistula (AVF) is the optimal vascular access for dialysis; however, the reported outcomes following AVF creation vary widely, with primary patency rates that range from 50% to 65% at 1 year. Many adaptations of the original procedure have been proposed to improve outcomes, but the evidence to support these is unclear and often conflicting. The aim of this article is to review the published literature on defined technical approaches to improve outcomes and determine the key technical aspects. Methods: Relevant literature was identified by searching Medline, Embase, and Cochrane databases using terms for arteriovenous fistula, technique, and modification. In addition, secondary referencing was performed. Studies including technical approaches or modifications were reviewed. All other reports of pre- or post-creation intervention/revisions/medication and not in English were excluded. Results: From 3302 records, 81 relevant studies were reviewed and referenced. Four main types of AVF procedure have been described: a traditional approach, piggyback straight-line on-lay technique (pSLOT), not-touch technique, and radial artery deviation and reimplantation (RADAR). Randomized trials have been performed in seven technical steps to optimize the outcome of the traditional AVF (control of blood vessels, intra-luminal probes, an excision arteriotomy, anastomosis technique, anastomotic angle, interrupted suture technique, blood vessel dilatation). Other techniques (pSLOT, not-touch, RADAR) have conflicting rationale and techniques, but still report excellent outcomes. Conclusions: This review does not support the concept of a single ‘ideal’ AVF operation that applies to all circumstances. Although there appear to be opposite philosophical views between all four techniques, all are marked by a thoughtful, adaptive, meticulous approach, implying that the key variable in determining the outcome is the surgeon, rather than a prescribed procedure.